Bibliometric analysis of scientific articles in public finance published in the spell electronic library between 2009 and 2019 (Research, Society and Development, 2020)
The article aimed to analyze the profile of articles on public finance published on the SPELL platform, in the period from 2009 to 2019. Bibliometric analysis is a way of analyzing scientific publications and books in a quantitative way. The research carried out was bibliographic and descriptive, with a bibliometric analysis with the help of Microsoft excel 2013. In the analysis of the results, the authors' gender, academic affiliation of the authors, year of audience, article genre, study area of the article were analyzed , magazine in which the publication was published and qualis of the magazine. It was noticed that the majority of authors in public finance are men, with academic affiliation in Brazilian public universities, being the genre of bibliographic articles, qualitative and quantitative, with a greater number of publications in the year 2013, being articles in the area of accounting and in magazines with high quality.